DNMT1 cooperates with MBD4 to inhibit the expression of Glucocorticoid‐induced TNFR‐related protein in human T cells. Issue 13 (10th June 2017) - Wang, Shuaiwei; Li, Yangyang; Zhu, Fangming; Lin, Fang; Luo, Xuerui; Zhao, Binbin; Zhang, Peng; Li, Dan; Gao, Yayi; Liang, Rui; Liu, Luyan; Tsun, Andy; et al.
Abstract : Glucocorticoid‐induced TNFR‐related protein (GITR) is constitutively expressed in T regulatory (Treg) cells and regulates their suppressive function. We identified two methylated CpG islands in the Gitr locus. Using a ChIP assay, we demonstrate that both DNMT1 and methyl‐CpG‐binding domain Protein 4 (MBD4) bind to the Gitr promoter. Moreover, knockdown of DNMT1 decreases the binding activity of MBD4. We observed much higher levels of both DNMT1 and MBD4 in human CD4 + CD25 − conventional T (Tconv) cells. Moreover, co‐overexpression of DNMT1 and MBD4 in Treg cells significantly inhibits GITR expression and impairs their suppressive activity. Our results reveal a novel molecular mechanism by which MBD4 inhibits GITR expression in a DNMT1‐dependent manner. Abstract :